Foetal outcome in pregnancy complicated with viral hepatitis - Thakur, Harshada S.; Maydeo, Niranjan; Kamble, Madhuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The purpose of this study is to study foetal outcome in pregnancy complicated with viral hepatitis, rate of NICU admission and foetal death. Methods: This is a cross sectional observational study undertaken in the Department of Obstetrics and Gynaecology at the tertiary care centre for the study period from October 2015 to October 2016 approved by ethical committee. Results: There were 6555 deliveries in study period of October 2015-2016 in which 54 patients were diagnosed with viral hepatitis in pregnancy. Out of 54 patients of viral hepatitis, 30 cases (55.55%) of Hepatitis E virus, 22 cases (40.74%) of Hepatitis B virus, 2 cases (3.7%) of Hepatitis C virus. No case was found for Hepatitis A virus infection. Higher incidence of NICU admission (56.66%), preterm delivery (36.66%) and intra uterine death (23.33%) was observed with Hepatitis E infection. Conclusions: Foetal outcome was poor in Hepatitis E virus followed by Hepatitis B virus. Acute viral hepatitis is more common cause of hepatitis in pregnancy. Hepatitis E virus was the most common cause of acute infection with adverse fetal outcome. Fetal loss including intra uterine death and preterm neonate was statistically significant with Hepatitis E viral infection. Health education, early diagnosis and multidisciplinary approach is the key to reduce foetal morbidity and mortality. As HBV infection in hepatitis in pregnancy is second most common cause of viral hepatitis, complete immunization against HBV in reproductive age group before first pregnancy is recommended.